1995
DOI: 10.1021/ma00125a003
|View full text |Cite
|
Sign up to set email alerts
|

Time-temperature superposition and linear viscoelasticity of polybutadienes

Abstract: A series of monodisperse polybutadienes has been used to perform mechanical relaxation measurements from the flow regime to the glassy state. Results on loss shear moduli have been analyzed within the framework of a coupling model. It has been found to represent well the frequency dependence in the glassy and terminal zones using a segmental motion coupling parameter Pa and an entanglement coupling parameter Pv. Moreover, our results on apparent shift factors resulting from time-temperature superposition are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 9 publications
7
81
1
Order By: Relevance
“…(16) by varying the C parameter in an attempt to fit literature terminal relaxation data for 1,4-polybutadienes and 1,2-polybutadienes which vary extensively in molecular weight. For 1,4 polybutadiene, we consider the data of Palade et al [42] and the results of Colby et al [23]. The studies of Carella et al [43] and Roovers and Toporowski [37] provide results for 1,2-polybutadiene which we can also analyze.…”
Section: Resultsmentioning
confidence: 98%
“…(16) by varying the C parameter in an attempt to fit literature terminal relaxation data for 1,4-polybutadienes and 1,2-polybutadienes which vary extensively in molecular weight. For 1,4 polybutadiene, we consider the data of Palade et al [42] and the results of Colby et al [23]. The studies of Carella et al [43] and Roovers and Toporowski [37] provide results for 1,2-polybutadiene which we can also analyze.…”
Section: Resultsmentioning
confidence: 98%
“…35,36,42,43 Since the terminal viscosity is determined primarily by the p ) 1 term, application of the coupling model heretofore employed the approximation of truncating the series in eq 9 to the first mode. Eq 9 then has the form of eq 3, which was used as an empirical fitting function by Tobolsky and co-workers 44 and more recently by Palade et al 45 These investigators reported that it gave a reasonably good fit to the terminal relaxation modulus of entangled polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The dependencies for other copolymers were of the same shape but shifted along the temperature axis in accordance with the difference in T g (Table I). The frequency dependence of the loss tangent peak temperature T was fit by the WLF equation [13][14] :…”
Section: Dynamic Mechanical Behaviormentioning
confidence: 99%